1997
DOI: 10.1002/jpln.19971600222
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and ammonium nutrition of plants: Effects on acid/base balance and adaptation of root cell plasmalemma H+ATPase

Abstract: The increase of rhizosphere pH in the course of nitrate nutrition results from H+ consumption in the external medium during uptake of NO3− in a H+ co‐transport and from internal OH− production during nitrate reduction. Synthesis of organic acids for NH4+ assimilation as well as strong partial depolarization of membrane potential with NH4+ uptake are the important reasons for rhizosphere acidification during ammonium nutrition. Despite differences in proton balance depending on N form, cytoplasmic pH changes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 47 publications
3
46
0
1
Order By: Relevance
“…When plants absorb NH 4 + , their roots secrete protons, thereby acidifying their rhizosphere and causing a release of P from the soil. However, in this study, we buffered the nutrient solution with 5 mM MES at pH 5.5, and at a stable pH, the hydrolytic activity or pumping activity of the H + -ATPase should be the same under both NH 4 + and NO 3 2 treatment (Schubert and Yan, 1997;Zhu et al, 2009). Furthermore, because of the absence of both soluble and insoluble P in the 2P hydroponic solution, the involvement of the pH is excluded.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When plants absorb NH 4 + , their roots secrete protons, thereby acidifying their rhizosphere and causing a release of P from the soil. However, in this study, we buffered the nutrient solution with 5 mM MES at pH 5.5, and at a stable pH, the hydrolytic activity or pumping activity of the H + -ATPase should be the same under both NH 4 + and NO 3 2 treatment (Schubert and Yan, 1997;Zhu et al, 2009). Furthermore, because of the absence of both soluble and insoluble P in the 2P hydroponic solution, the involvement of the pH is excluded.…”
Section: Discussionmentioning
confidence: 93%
“…NH 4 + and NO 3 2 are the two major N sources that are taken up by plant roots (Marschner, 1995;Falkengren-Grerup et al, 2000). In general, with the absorption of NH 4 + by plants, the related proton release decreases the pH of the rhizosphere (Wang et al, 1993;Mistrik and Ullrich, 1996;Schubert and Yan, 1997;Zhao et al, 2009), which leads to increased solubility and uptake of P by the plants (Sarkar and Jones, 1982;Hoffmann et al, 1994). The opposite appears to be true with the uptake of N in the form of NO 3 2 (Smiley, 1974;Marschner and Römheld, 1983;Moorby et al, 1985;Watanabe et al, 1998).…”
mentioning
confidence: 99%
“…Because of the high proton sensitivity of common bean, Massot et al (1990) classified six genotypes for Al resistance using a solution pH of 4.8, but without control of pH and also without monitoring Al activity in solution. The high proton sensitivity of common bean may be related to a low efficiency of the plasma-membrane proton ATPase (Yan et al, 1992(Yan et al, , 1998, and thus the inability to maintain the cytosolic pH leading to cell injury (Schubert and Yan, 1997).…”
Section: Adaptation Of the Basal Incubation Medium Used For Maize To mentioning
confidence: 99%
“…If this holds true, an adaptation of plasma membrane H ϩ ATPase in active proteoid roots can be expected. In fact, it has been demonstrated that plasma membrane H ϩ ATPase responds to a number of environmental factors, such as saline stress (Niu et al, 1993), low solution pH (Yan et al, 1998), nutrient supply (Schubert and Yan, 1997), and Fe deficiency (Delló rto et al, 2000). It is feasible to hypothesize that plasma membrane H ϩ ATPase of proteoid root cells may be involved in the release of citric acid and possibly plays a central role in the adaptation of white lupin to P deficiency.…”
mentioning
confidence: 99%